2022
DOI: 10.3390/w14244011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Surface Energy Balance Model for Partially Wetted Surfaces: Drip and Micro-Sprinkler Systems in Hazelnut Orchards (Corylus Avellana L.)

Abstract: A multi-layer surface energy balance model was previously developed to estimate crop transpiration (T) and soil evaporation (E) in orchards partially wet by micro-irrigation systems. The model, referred to as SEB-PW, estimates latent (λE), sensible (H), and soil heat fluxes (G) and separates actual evapotranspiration (ETa) into dry and wet soil E and crop T. The main goal of this work was to evaluate the ability of the SEB-PW model to estimate ETa and analyze the diurnal and seasonal dynamics of E and T in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In this way, the intensity of light is detected at different heights of the plant and is compared with the light measured in full sunlight, revealing the light interception by the tree canopy. This parameter is important because there is a direct relationship between cumulative ET and PAR (photosynthetically active radiation) light interception by the tree canopy; a higher PAR light interception value corresponds to higher ET [25]. To obtain an estimation of the light interception by the whole tree canopy, the canopy light interception is expressed as the mean value of all data recorded at different distances from the trunk and tree heights.…”
Section: Manual Measurementsmentioning
confidence: 99%
“…In this way, the intensity of light is detected at different heights of the plant and is compared with the light measured in full sunlight, revealing the light interception by the tree canopy. This parameter is important because there is a direct relationship between cumulative ET and PAR (photosynthetically active radiation) light interception by the tree canopy; a higher PAR light interception value corresponds to higher ET [25]. To obtain an estimation of the light interception by the whole tree canopy, the canopy light interception is expressed as the mean value of all data recorded at different distances from the trunk and tree heights.…”
Section: Manual Measurementsmentioning
confidence: 99%
“…Souto et al [6] showed the ability of the SEB-PW (Surface Energy Balance Model for Partially Wetted) model to estimate actual evapotranspiration (Eta) and analyze the diurnal and seasonal dynamics of evaporation (E) and transpiration (T) in two Corylus avellana L. orchards using drip or micro-sprinkler irrigation systems. The study results indicated that the used model enhanced soil E by allowing the wetted and non-wetted areas.…”
Section: Summary Of This Special Issuementioning
confidence: 99%